Analysis of Ecotourism Development Potential in Paseban Savana Jember, East Java - Fauzi, M. Amir; Saputra, Muhammad Ichsan Eko; Indallah, M. Najib (Aspirasi Masyarakat Intelektual Islam Nusantara, 2023)
Savanna is a low-rainfall ecosystems. This habitat is frequently dominated by lush green grass. There is a savanna in Paseban Village, Kencong District, Jember Regency that is notable for nature tourism since it has an appealing and natural sense. The purpose of this study is to investigate the potential for ecotourism development in Paseban Savana, Jember, East Java. This study is qualitative in design. Interviews were utilized to acquire data. Locals and visitors are the source of information. This approach is designed to collect data on the many types of savanna utilization that are currently in use. In addition to interviews, this study included the documentation approach. The investigation discovered that this area was previously restricted to territory that was barren and parched, but that heavy continuous rain eventually turned this land green. Because of the natural splendor of the green savanna, an increasing number of visitors visit. Tourists typically visit to snap photographs. However, as the number of tourists increases, so does the garbage problem. Given that this savanna has recently grown increasingly busy with tourists, there is no management in place to enforce cleanliness and other rules. We suggest appointing management, providing trash cans, and shielding plant-containing areas from harm caused by visitors.